Case report: Non-thrombotic iliac vein lesion: an unusual cause of unilateral leg swelling in a patient with endometrial carcinoma - Zeman, Jan; Kompella, Ritika; Lee, JuYong; Kim, Agnes S. (Frontiers in Cardiovascular Medicine, 2023)
81-year-old female presented with subacute right lower extremity edema due to iliac vein compression by a markedly enlarged external iliac lymph node later identified as newly relapsed metastatic endometrial carcinoma. The patient underwent a full evaluation of the iliac vein lesion and cancer and had an intravenous stent placed with complete resolution of symptoms post-procedure.